Bandar Lampung City Government Policy in Provision of Green Open Space Based on Regional Spatial Plan - Mahendra, Fazri; Akib, Muhammad; Triono, Agus (Zona Law And Public Administration Indonesia, 2024)
For now, Bandar Lampung City already has Green Open Space (RTH) but it is still insufficient as explained in the RTRW Regional Regulation where public RTH must have an area of at least 20% of the Bandar Lampung City area. Although there is already an RTH in Bandar Lampung City, until now the RTH in Bandar Lampung City has not changed much, even there are many RTH that have been converted into housing or buildings. The purpose of this study is to analyze the policy of providing Green Open Space (RTH) by the Bandar Lampung City Government and evaluate the factors that cause RTH in Bandar Lampung City to be unfulfilled. This study used normative and empirical research. The data used are primary data and secondary data with data collection techniques, namely literature studies and field studies through interviews. The result of this study is that the policy of providing RTH in Bandar Lampung City has been regulated in the Spatial Planning Law and Regional Spatial Plan (RTRW) of Bandar Lampung City which in the regulation requires the number of RTH to be 30%, namely 20% public and 10% private. The unfulfilled RTH in Bandar Lampung City is due to the absence of good collaboration between the Bandar Lampung City Government, related parties, and the community, changing regulations and regulations, land use change and massive concrete infrastructure development in Bandar Lampung City. The efforts made by the Bandar Lampung City Government in fulfilling the provision of RTH are to maintain and maintain the availability of RTH that is still owned, establish mangrove forests as RTH, make RTH along coastal boundaries, river borders, and along roads, and the Government also requires related parties when there is a housing / building construction must provide 10% RTH of the development land area